Boron Foliar Application Improves Growth, Yield and Grain Quality of Maize - Bayar, Jalal; Shah, Shahen; Khan, Waleed; Okla, Mohammad K.; Alwasel, Yasmeen A.; Saleh, Ibrahium A.; Abdelgawad, Hamada; Rahim, Waqas; Iqbal, Babar; Jalal, Arshad [UNESP] (HARD Publishing Company, 2024)
Balanced nutrition is the key to higher quality crop production. Micronutrients, especially boron (B) have an important role in various physiological processes and stress tolerance while its deficiency could affect the yield and quality of crop plants. In this context, this study investigated the significance of foliar B application at various growth stages on maize yield components, yield, and grain B content. The treatments consisted of boron foliar application levels (0, 0.5, 1, 1.5 and 2%) at different growth stages (V4 = fourth leaf stage, V8 = eighth leaf stage and VT = tasseling stage) during summer 2021 and 2022. The results revealed that plant height, leaf area plant-1, leaf area index, plants at harvest, ear length, grains ear-1, thousand grains weight, shelling percentage, biological yield, grain yield and harvest index were increased with 1 % B foliar spray compared to other levels. In addition, ear length, grains ear-1, thousand grains weight, shelling percentage, biological yield, grain yield and harvest index were increased with B foliar application at VT (tasseling stage) compared to other stages. It was concluded that the application of 1% foliar boron (1.28 kg B ha-1) i.e. 7.32 kg H3 BO3 at tasseling stage improved growth, yield and yield components of maize.
Keywords: boron; foliar application; growth stages; maize yield; yield components